Vocational High School Students’ Learning Difficulty in ESP - Arroyyani, Risa; Maryani, Maryani (Sintuwu Maroso Journal of English Teaching, 2025)
As part of English for Specific Purposes, English for nursing presents challenges and obstacles that cannot be overlooked. The difficulties experienced by students in learning English in the classroom significantly affect the success of their mastery of the language. This study aims to identify the difficulties faced by Vocational High School students in learning English for Specific Purposes, particularly in the nursing major. This research is a qualitative descriptive study using research instruments obtained from questionnaires and interviews. The respondents of this study are 26 students from the 12th grade of vocational high school, specializing in nursing. The research instruments include questionnaires and structured interviews. Out of the 26 students, two students participated in follow-up interviews to support the data from the questionnaires. The findings indicate that the students’ difficulties are in both internal and external factors. The internal factors include difficulties in linguistic aspects such as pronunciation, reading, vocabulary, speaking, grammar, translation, as well as psychological aspects such as anxiety. External factors include difficulties related to teaching methods and materials.